Human intrahepatic CD69 + CD8+ T cells have a tissue resident memory T cell phenotype with reduced cytolytic capacity - Femke Stelma (Nature Portfolio, 2017)
Abstract Tissue resident memory T cells (TRM) have been identified in various tissues, however human liver TRM to date remain unidentified. TRM can be recognized by CD69 and/or CD103 expression and may play a role in the pathology of chronic hepatitis B (CHB) and hepatitis C virus infection (CHC). Liver and paired blood mononuclear cells from 17 patients (including 4 CHB and 6 CHC patients) were isolated and CD8+ T cells were comprehensively analysed by flowcytometry, immunohistochemistry and qPCR. The majority of intrahepatic CD8+ T cells expressed CD69, a marker used to identify TRM, of which a subset co-expressed CD103. CD69 + CD8+ T cells expressed low levels of S1PR1 and KLF2 and a large proportion (>90%) was CXCR6+, resembling liver TRM in mice and liver resident NK cells in human. Cytotoxic proteins were only expressed in a small fraction of liver CD69 + CD8+ T cells in patients without viral hepatitis, however, in livers from CHB patients more CD69 + CD8+ T cells were granzyme B+. In CHC patients, less intrahepatic CD69 + CD8+ T cells were Hobit+ as compared to CHB and control patients. Intrahepatic CD69 + CD8+ T cells likely TRM which have a reduced cytolytic potential. In patients with chronic viral hepatitis TRM have a distinct phenotype.